Karbamazepinin kore tedavisindeki yeri - (:unkn) unknown (My University, 2006)
Amaç: Çocuklarda kore tedavisinde karbamazepinin etkinliğini incelemek. Hastalar ve yöntem: Kore tanısı alanö ortalama yaşları 11.5 yaş olan üçü kız, üçü erkek altı hasta karbamazepin (5-20 mg/kg/gün)ile tedavi edildi. Tedaviye yanıt el yazısı ve Arşimed spiral testindeki değişiklikler temel alınalarak değerlendirildi. Sonuçlar: Tüm hastalarda ilk iki hafta içinde belirgin klinik düzelme gözlendi. Dört hastada kore tamamen kaybolurken, iki hastada belirgin iyileşme görüldü. Yan etki saptanmadı. Sonuç: Karbamazepin çocuklarda kore tedavisinde etkili ve güvenilir bulunmuştur.

Objective: To investigate the efficacy of carbamazepine in children with chorea. Patients and method: Six children (three boys, three girls, mean age 11.5 years) with the diagnosis of chorea were treated with carbamazepine (5-20 mg/kg/day). Response to the treatment was assessed based on improvement of hand-writing and Archimedes spiral test. Results: Clinical improvement was observed in all children within the first two weeks. Chorea totally disappeared in four patients. In other two patients chorea did not disappeared totally, however markedly improvement was observed. No side effects were seen. Conclusion: Carbamazepine is an efficient and safe drug in the treatment of chorea in children.
Carbamazepine in the treatment of chorea
Keywords: Hematoloji; Tıbbi Araştırmalar Deneysel; Ortopedi; Pediatri